2017
DOI: 10.1128/jcm.00144-17
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Emerging Vaccine-Related Polioviruses by Deep Sequencing

Abstract: Oral poliovirus vaccine can mutate to regain neurovirulence. To date, evaluation of these mutations has been performed primarily on culture-enriched isolates by using conventional Sanger sequencing. We therefore developed a culture-independent, deep-sequencing method targeting the 5′ untranslated region (UTR) and P1 genomic region to characterize vaccine-related poliovirus variants. Error analysis of the deep-sequencing method demonstrated reliable detection of poliovirus mutations at levels of <1%, depending … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…In a previous study [18], we have described that the presence of mutant variants and variants per sample was quite low in a subset of the samples we collected; we therefore consider that it is unlikely that there were any VDPVs among our samples.…”
Section: Discussionmentioning
confidence: 98%
“…In a previous study [18], we have described that the presence of mutant variants and variants per sample was quite low in a subset of the samples we collected; we therefore consider that it is unlikely that there were any VDPVs among our samples.…”
Section: Discussionmentioning
confidence: 98%
“…Research has shown the importance of analyzing the complete genome for enteroviruses ( Oberste et al, 2004 ; Joffret et al, 2012 ) because nucleotidic differences and inter and intra-typic recombination events in non-structural regions differentiate types and lineages ( Lukashev et al, 2003 ; Simmonds, 2006 ; Combelas et al, 2011 ). The amplification and sequencing of whole genomic sequences of strains belonging to EV-A, -B, and -C species using generic and specific primers were successfully performed ( Tan et al, 2015 ; Bessaud et al, 2016 ; Montmayeur et al, 2017 ; Sahoo et al, 2017 ). One particular study aimed to isolate polioviruses using random amplification and NGS to better optimize current protocols for whole genome sequencing and identification of a variety of vaccine-derived polioviruses ( Montmayeur et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Next generation sequencing (NGS) methods offer a new powerful sequencing tool for the identification and characterization of enteroviruses. This has been successfully used to sequence partial or whole genome sequences of poliovirus and of enteroviruses species C ( Bessaud et al, 2016 ; Montmayeur et al, 2017 ; Sahoo et al, 2017 ). Additionally, a generic assay for whole genome amplification and deep sequencing of enterovirus A71 was published ( Tan et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, genetic sequencing using the Sanger technique was performed on these OPV-positive samples to rule out the possibility of false positives due to other enteroviruses [ 4 ].…”
Section: Methodsmentioning
confidence: 99%